Pengaruh Model Project Based Learning Berbantuan Media Audiovisual Terhadap Keterampilan Menulis Teks Berita Siswa - Dila Azahra; Mita Domi Fella Henanggil; Afnita Afnita; Ridha Hasnul Ulya (Paedagogie, 2026)
This study aims to describe the news writing skills of seventh-grade students at SMPN 15 Padang before and after using the Project Based Learning (PjBL) model assisted by audiovisual media, and to analyze the effect of implementing the Project Based Learning (PjBL) model assisted by audiovisual media on students' news writing skills. This study employed a quantitative approach with a pre-experimental approach. The research design used a one-group pretest and posttest design, consisting of one sample class. The sampling technique used was purposive sampling. The data obtained were news writing skill scores, which were then converted into grades. The results showed that the news writing skills of seventh-grade students at SMPN 15 Padang after implementing the Project Based Learning (PjBL) model assisted by audiovisual media improved compared to before the treatment. The average score before the implementation of the Project Based Learning (PjBL) model assisted by audiovisual media was 52.15, qualifying as Almost Sufficient (HC), while the average score after the treatment increased to 83.40, qualifying as Good (B). Based on the results of the statistical test, the calculated t value > t table (15.86 > 1.70) was obtained at a significance level of 0.05 with a 95% confidence level. Thus, it can be concluded that the Project Based Learning (PjBL) model assisted by audiovisual media has a significant effect on students' news text writing skills.